Chemical Biology of the Tropics An Interdisciplinary Approach - Vivanco, Jorge M.; Weir, Tiffany; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
The mystique of the rainforest has captured the imaginations of generations of young people, explorers, authors, and biologists. It is a delicate ecosystem whose myriad sounds and smells, whose vibrancy of life, is balanced by constant cycles of death and decay. It is a place of fierce competition where unusual partnerships are forged and creative survival strategies are the norm. In this book, you will meet the scientific pioneers who first attempted to quantify and understand the vast diversity of these tropical forests, as well as their successors, who utilize modern tools and technologies to dissect the chemical nature of rainforest interactions. This book provides a general background on biodiversity and the study of chemical ecology before moving into specific chemical examples of insect defenses and microbial communication. It finishes with first-hand accounts of the trials and tribulations of a canopy biology pioneer and a rainforest research novice, while assessing the state of modern tropical research, its importance to humanity, and the ecological, political, and ethical issues that need to be tackled in order to move the field forward.
Biodiversity -- Chemical Ecology: Definition and Famous Examples -- Chemical Defenses of Insects: A Rich Resource for Chemical Biology in the Tropics -- Defensive Behaviors in Leaf Beetles: From the Unusual to the Weird -- Microbes: A New Frontier in Tropical Chemical Biology -- Out on a Limb - True Confessions of a Bug Detective -- So, You Want to do Research in the Rainforest?.
Keywords: Life sciences; Biochemistry; Plant Ecology; Botany; Life Sciences; Plant Biochemistry; Plant Ecology; Plant Sciences